2020
DOI: 10.3389/fphar.2020.00186
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin Enhances the Anticancer Effect on Non-Small Cell Lung Cancer While Reducing the Cardiotoxicity of Adriamycin

Abstract: Digoxin is widely used to treat heart failure. Epidemiological studies suggested it might be used as an anticancer drug or sensitizing agent for cancer therapy. Adriamycin is a wellknown anticancer drug, but often causes cardiotoxicity which limits its use. We recently investigated the anticancer effects of digoxin alone or in combination with adriamycin on human non-small cell lung cancer in vitro and in vivo. Digoxin reduced the viability of A549 and H1299 cells in vitro, increased DNA damage by promoting RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 37 publications
2
32
0
1
Order By: Relevance
“…After treatment with BKM120 or/and rucaparib for 12/24 h, U251 and U87MG cells were collected and subjected to alkaline comet assay for detection of both SSBs and DSBs as we described previously 42 . The cells (1 × 10 5 /ml) were combined with molten LMAgarose at a ratio of 1:10 (v/v), and 50 µl of cell suspension was immediately added onto comet slides.…”
Section: Methodsmentioning
confidence: 99%
“…After treatment with BKM120 or/and rucaparib for 12/24 h, U251 and U87MG cells were collected and subjected to alkaline comet assay for detection of both SSBs and DSBs as we described previously 42 . The cells (1 × 10 5 /ml) were combined with molten LMAgarose at a ratio of 1:10 (v/v), and 50 µl of cell suspension was immediately added onto comet slides.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are few reports on this aspect. Besides, digoxin also showed good antitumor activity in multiple cancer types [26][27][28]. Therefore, we used digoxin as a positive control and found that both THB and it have a strong inhibitory effect on lung cancer, but THB appeared to show better tumor suppressive effect in NSCLC mouse model without signi cant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the antitumor effect of these anti-proliferative agents can be evaluated alongside any cardiac toxicity secondary to cancer therapy. In one study, zebrafish and mice xenograft models were injected with A549 cells and then used to assess co-treatment of doxorubicin with digoxin, an inotropic agent used in heart failure [ 65 ]. Co-treatment with digoxin enhanced the antitumor effect of doxorubicin in both organisms and reduced cardiotoxicity caused by doxorubicin in mice, as quantified by the heart size and cardiomyocyte size postmortem.…”
Section: Zebrafish As a Model To Study Cancer Biologymentioning
confidence: 99%